Performance evaluation and characterization of different photovoltaic technologies under the coastal, desertic climate conditions of Lima, Peru - Conde L.A. (2020)
This work presents the firsts results of the experimental characterization campaign under outdoor conditions carried out with three different photovoltaic (PV) module technologies: Standard poly-crystalline silicon (poly-Si) aluminum back surface field (Al-BSF) cells, mono-crystalline (c-Si) Heterojunction with Intrinsic Thin-Layer (HIT) cells, and amorphous and microcrystalline silicon (a-Si/µc-Si) thin-film tandem cells. We studied the behavior of these PV technologies and their performance in Lima's desertic and coastal climate during the period from May 2019 to July 2019. For this study, a new outdoor-PV laboratory was implemented at the Pontificia Universidad Católica del Perú (PUCP) with the help of the IDEA research group of the University of Jaén (UJA), Spain. The laboratory enables the characterization of PV modules by extracting the electrical parameters from the current-voltage (I-V) curve under outdoor conditions and by measuring the irradiance, the spectral distribution, the panel temperature, and the weather conditions. As a first step, the nominal maximum power of the PV modules under standard test conditions is obtained from the outdoor data. Then, an analysis of the different PV technologies' performance under the local climate conditions is presented by applying the Osterwald and the constant fill factor methods to compare the modeled and experimental maximum power. © 2019. The Authors. Published by International Solar Energy Society Selection and/or peer review under responsibility of Scientific Committee